First record of Cryptophion Viereck, 1913 (Ichneumonidae: Campopleginae) from Colombia, with description of a new species - Santos, Alvaro Doria Dos; Onody, Helena Carolina; Palacio, Edgard (Zootaxa, 2022)
The genus Cryptophion Viereck, 1913 includes eight Neotropical species distributed in Central and South America. Herein the genus is recorded for the first time in Colombia and a new species, Cryptophion flavonigrovittatus Santos, Onody & Palacio sp. nov. is described. In addition, Cryptophion spinozai and Cryptophion guilhermoi are reported for the first time for Colombia. An identification key is also provided for all species of the genus.